Building the Strategic National Stockpile Through the NIAID Radiation Nuclear Countermeasures Program. Issue 1 (26th December 2013) - Rios, Carmen I.; Cassatt, David R.; DiCarlo, Andrea L.; Macchiarini, Francesca; Ramakrishnan, Narayani; Norman, MaiâKim; Maidment, Bert W.; Shankar, Gita N.; Moos, Walter H.
Abstract The possibility of a public health radiological or nuclear emergency in the United States remains a concern. Media attention focused on lost radioactive sources and international nuclear threats, as well as the potential for accidents in nuclear power facilities (e.g., Windscale, Three Mile Island, Chernobyl, and Fukushima) highlight the need to address this critical national security issue. To date, no drugs have been licensed to mitigate/treat the acute and longâterm radiation injuries that would result in the event of largeâscale, radiation, or nuclear public health emergency. However, recent evaluation of several candidate radiation medical countermeasures (MCMs) has provided initial proofâofâconcept of efficacy. The goal of the Radiation Nuclear Countermeasures Program (RNCP) of the National Institute of Allergy and Infectious Diseases (National Institutes of Health) is to help ensure the government stockpiling of safe and efficacious MCMs to treat radiation injuries, including, but not limited to, hematopoietic, gastrointestinal, pulmonary, cutaneous, renal, cardiovascular, and central nervous systems. In addition to supporting research in these areas, the RNCP continues to fund research and development of decorporation agents targeting internal radionuclide contamination, and biodosimetry platforms (e.g., biomarkers and devices) to assess the levels of an individual's radiation exposure, capabilities that would be critical in a mass casualty scenario. New areas of research within the program include a focus on special populations, especially pediatric and geriatric civilians, as well as combination studies, in which drugs are tested within the context of expected medical care management (e.g., antibiotics and growth factors). Moving forward, challenges facing the RNCP, as well as the entire radiation research field, include further advancement and qualification of animal models, dose conversion from animal models to humans, biomarker identification, and formulation development. This paper provides a review of recent work and collaborations supported by the RNCP.